Perencanaan Pengembangan Kawasan Perkebunan Kopi Arabika di Kabupaten Bener Meriah - Ilham iwan Tona; Boedi Tjahjono; Iskandar Lubis (P4W LPPM IPB, 2023)
Regional development is one of the efforts to increase socio-economic growth and reduce regional disparities. The Arabica coffee variety is one of the mainstay commodities in this region and a source of income for the people in Bener Meriah Regency. Land use planning based on superior commodities is expected to be able to overcome problems related to the effectiveness of land use, through this land use planning, land allocation will be determined according to its designation. The purpose of this study was to formulate a strategy in planning the development of Arabica coffee plantation areas in Bener Meriah Regency, through the stages of identifying the distribution of coffee plantations, analyzing potential availability and land suitability, analyzing agribusiness systems and analyzing the level of availability of regional facilities and infrastructure. The results of the analysis show that the distribution of Arabica coffee plantations in Bener Meriah Regency reaches an area of ​​46,167 ha. As for the extensive development of coffee plantations, this district has a suitable land area of ​​7,401.1 ha. The most dominant land suitability class is N with a height limiting factor with an area of ​​3,581.92 ha. Farming coffee farmers carried out by farmers is efficient because it has an R/C ratio = 2. The availability of facilities and infrastructure shows that the 2 sub-districts that have the highest level of service and development, namely Bukit District and Weh Pesam District, are classified as developed or Hierarchy I. Based on the AWOT, the suggested alternative strategy for the development of Arabica coffee plantations in Bener Meriah Regency is to optimize the availability of land and the use of infrastructure needed to support the improvement of the quality of plants and products.